EDUCATIONAL PROGRAMME "MEDIA COMMUNICATIONS": DOMESTIC AND FOREIGN EXPERIENCE IN IMPLEMENTATION - Yuliya A. Eliseyeva; Pentti Yu. Tenhunen (National Research Mordova State University, 2016)
Introduction: the attribute of information society is the availability of the developed system of media communications i.e. the processes of creation, broadcasting, exchange of information through various channels by using various communicative means (verbal, sound, and visual). The traditional (the press, radio, television) and new (Internet) media determine tendencies of sociocultural development. Management of media communications has caused the emergence of new training direction "Media communications" in structure of country's higher education. The paper is devoted to specifics of implementation of the appropriate educational programme at the domestic and foreign higher school. The authors propose the four-component competence-based model of a media professional with due account for best pedagogical practices in the considered area. Materials and Methods: the authors draw on systemic, interdisciplinary, competence-based approaches; methodology of the system; terminological, comparative analysis; classification; con-ceptual modeling, and benchmarking. Results: the media communications are system with sophisticated structure. The development of adequate didactic means is required to teach and master it. The experience of implementation of the considered programme (bachelor degree level) at National research university "Higher School of Economics" allows to highlight three key competences: creative, technological and managerial. The authors have analyzed experience of the leading universities (The London university Gold-smith, Great Britain; Technical university of Ilmenau, Germany; Stockholm University, Sweden; Helsinki University, Finland; University Colorado, USA) and substantiate the necessity for identifying the forth one - innovation research competence that ensures adaptation to inevitable transformation of media enviro nment. Discussion and Conclusions: the media communications are a prospective area of training of specialists. Universality and transprofessionalism as fundamental professional attributes of prospective graduates require deep methodological and methodical elaboration of the content and structure of the profile educational programme. The proposed four-component competence-based model of a media professional will be tried out at National Research Mordovia State University.